Physical Fitness Survey of Members of the Communication and Electronics Service of the Indonesian Navy Headquarters - Lili Sadeli; Bachtiar Bachtiar; Firman Septiadi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This survey aims to measure the level of physical fitness of members of the Communication and Electronics Service at the Navy Headquarters. Data was obtained through a series of physical fitness tests which included the 12-minute Run Test, Pull up, Sit up, Push up and Shuttle run. The survey results are expected to provide an accurate picture of the physical condition of personnel and become the basis for developing a more effective physical development program. This research is a descriptive study with survey and measurement test methods. The subjects of this research data are members of the Communication and Electronics Service of the Navy Headquarters, age category 29 to 40 years as many as 30 respondents. Data analysis techniques using fiber percentages calculate the maximum and minimum values and standard deviations. The results showed that most of the physical fitness of members of the Communication and Electronics Service of the Navy Headquarters was good. In detail the results obtained; 14 people (46.7%) in the Good category, 13 people (43.3%) in the Sufficient category and 3 people (3.0%) in the Less category, while for the Very Good and Less category there is no (0%).